Analysis of Attitudes and Mathematical Abilities Based on Gender in Muhammadiyah Merauke Junior High School Students - Dewi Puji Lestari; Markus Palobo; Kamariah Kamariah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This study evaluates how the attitudes and mathematical abilities of Muhammadiyah Merauke junior high school students are influenced by gender differences. The research uses a descriptive-comparative quantitative approach involving 28 eighth-grade students (15 males, 13 females). Data were collected through a questionnaire on attitudes toward mathematics and a mathematical ability test. The results show that male students tend to have slightly more positive attitudes compared to females. However, the mathematical abilities of both groups are considered very low. No significant effect of gender on mathematical ability results was found. The findings of this study suggest the need for enjoyable and contextual learning to improve students' mathematical abilities and motivation without gender bias.